ICT Update 76: Mobile finance - next stop for agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2014)
ICT Update is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. This issue focuses on agricultural mobile finance.